Effects of placental growth factor deficiency on behavior, neuroanatomy, and cerebrovasculature of mice - Kay, Vanessa R. (Physiol Genomics, 2018)
Preeclampsia, a hypertensive syndrome occurring in 3–5% of human pregnancies, has lifelong health consequences for fetuses. Cognitive ability throughout life is altered, and adult stroke risk is increased. One potential etiological factor for altered brain development is low concentrations of proangiogenic placental growth factor (PGF). Impaired PGF production may promote an antiangiogenic fetal environment during neural and cerebrovascular development. We previously reported delayed vascularization of the hindbrain, altered retinal vascular organization, and less connectivity in the circle of Willis in Pgf(−/−) mice. We hypothesized Pgf(−/−) mice would have impaired cognition and altered brain neuroanatomy in addition to compromised cerebrovasculature. Cognitive behavior was assessed in adult Pgf(−/−) and Pgf(+/+) mice by four paradigms followed by postmortem high-resolution MRI of neuroanatomy. X-ray microcomputed tomography imaging investigated the three-dimensional cerebrovascular geometry in another cohort. Pgf(−/−) mice exhibited poorer spatial memory, less depressive-like behavior, and superior recognition of novel objects. Significantly smaller volumes of 10 structures were detected in the Pgf(−/−) compared with Pgf(+/+) brain. Pgf(−/−) brain had more total blood vessel segments in the small-diameter range. Lack of PGF altered cognitive functions, brain neuroanatomy, and cerebrovasculature in mice. Pgf(−/−) mice may be a preclinical model for the offspring effects of low-PGF preeclampsia gestation.